An Information System Pattern for Cooperative Management in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2022)
The purpose of research was to develop and assess the suitability of an information system pattern for cooperative management in thai supply chain. The sample consisted of ten experts that were selected by simple random sampling The research was a purposive sampling technique.. Data analysis was the average mean and standard deviation. The research tool was questionnaire assessing the suitability of an information pattern for cooperative management in thai supply chain comprises six main components, namely suppliers, Cooperative, Distribution, Retailers, customer. The results from experts agreement of an information system pattern for cooperative management in thai supply chain showed high appropriateness and can develop database the tasks.